2016
DOI: 10.1186/s12915-016-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Wnt expression identifies a highly conserved developmental transition in flatworms

Abstract: BackgroundEarly developmental patterns of flatworms are extremely diverse and difficult to compare between distant groups. In parasitic flatworms, such as tapeworms, this is confounded by highly derived life cycles involving indirect development, and even the true orientation of the tapeworm antero-posterior (AP) axis has been a matter of controversy. In planarians, and metazoans generally, the AP axis is specified by the canonical Wnt pathway, and we hypothesized that it could also underpin axial formation du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(106 citation statements)
references
References 79 publications
7
99
0
Order By: Relevance
“…Similar to what has been observed in planarians 18 , tapeworms 19 , and acoels 20 , we find that many well-characterized morphogens that regulate wnt (Extended Data Fig 4a-d) and tgfb signaling (Extended Data Fig. 4e-h) are predominantly expressed in muscle and neuronal cells.…”
Section: Figsupporting
confidence: 84%
“…Similar to what has been observed in planarians 18 , tapeworms 19 , and acoels 20 , we find that many well-characterized morphogens that regulate wnt (Extended Data Fig 4a-d) and tgfb signaling (Extended Data Fig. 4e-h) are predominantly expressed in muscle and neuronal cells.…”
Section: Figsupporting
confidence: 84%
“…As a direct result of the unveiling of the complete genomes of the Echinococcus spp., several metabolic pathways have been explored, and other inhibitors are currently being studied (177,(282)(283)(284)(285)(286)(287). Nilotinib, an ABL (Abelson murine leukemia viral oncogene homologue)-tyrosine kinase inhibitor, and everolimus, a serine/threonine kinase inhibitor, caused alterations of E. multilocularis metacestode vesicles in vitro; however, neither of these compounds resulted in any reduction of parasite growth in E. multilocularis-infected mice, and combined application of the kinase inhibitors with ABZ did not lead to synergistic or additive treatment efficacy (282).…”
Section: Improving Diagnosis and Drug Treatment Of Echinococcosismentioning
confidence: 99%
“…This evolutionarily conserved pathway regulates crucial aspects of cell fate determination, cell migration, cell polarity, neural patterning and organogenesis in metazoan embryonic development [50]. E. multilocularis and other flatworms possess genes associated with each of the three known Wnt pathways [51,52], and recently Koziol et al [53] showed that the Wnt pathway is involved in anterior-posterior specification in E. multilocularis larvae. In concordance with our results, this signalling pathway has recently also been shown to be regulated by miRNAs in the platyhleminth S. japonicum [22].…”
Section: Gene Id Annotationmentioning
confidence: 99%